Considerations over the phase variation of VLF signals received at São José dos Campos - SP - Brazil - Luiz Alberto Vieira Dias (1968)
The phase variation of the signals in the band of VLF give us some information about the D region of the ionosphere. We prepared a study with the experimental data obtained at Sao Jose dos Campos, SP, Brasil (SJC)from two transmitters at different places. The location of the transmitters are Jim Creek, Washington, U.S.A. (NLK) and Trinidad (OMEGA). The diurnal variation of phase presents the same characteristics for both paths, while the seasonal variation of phase presents different behavior for the two paths. A possible reason to explain this difference is given by the difference of behavior of the seasonal ionization and loss in the different geographical latitudes of the D region. The occurence of sudden phase anomalies (SPA) is also different in the two paths. Suggestions are made to explain these features.